Karakteristik Bio Oil yang Menggunakan Bahan Baku Cangkang Kelapa Sawit dan Diproses dengan Metode Pirolisis - Azhar Basyir Rantawi (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Palm oil shell biomass has the potential to be converted into bio oil, based on its content such as lignocellulose content (lignin, hemicellulose and cellulose). To get this bio oil product can be done through the pyrolysis process, using a temperature of 150°C with a sampling time span of 20 minutes, 30 minutes and 40 minutes. The experimental result showed that the characteristic of bio oil in a 20 minutes sample had better quality result, ie with an average density value of 1.0286 (gr/ml), pH 3.03, and blackish brown color.